2019
DOI: 10.1016/j.jiec.2018.12.037
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of water-immiscible organic solvents in the production of furfural from xylose and birch hydrolysate

Abstract: Furfural (FUR) was produced from xylose using a biphasic batch reaction system. Water-immiscible organic solvents such as isophorone, 2-methyltetrahydrofuran (2-MTHF) and cyclopentyl methyl ether (CPME) were used to promptly extract FUR from the aqueous phase in order to avoid the degradation to humins as largely as possible. The effect of time, temperature, organic solvent and organic-to-aqueous ratio on xylose conversion and FUR yield were investigated in auto-catalyzed conditions. Experiments at three tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 66 publications
4
25
0
Order By: Relevance
“…7 for reacting batches, it can be seen that both methyl propionate and EtOAc show better values of R than H 2 O-DMSO/MIBK-2-BuOH and H 2 O-DMSO/DCM at 170°C 78 or H 2 O/MeTHF and H 2 O/CPME at 190°C. 114 On the contrary, the use of isophorone at 190°C as EP gives similar distribution coefficients ranging between 7 and 9, 114 thus being comparable to the two proposed solvents.…”
Section: Experimental Comparison With Cosmo-rs Predictions and Othermentioning
confidence: 80%
See 4 more Smart Citations
“…7 for reacting batches, it can be seen that both methyl propionate and EtOAc show better values of R than H 2 O-DMSO/MIBK-2-BuOH and H 2 O-DMSO/DCM at 170°C 78 or H 2 O/MeTHF and H 2 O/CPME at 190°C. 114 On the contrary, the use of isophorone at 190°C as EP gives similar distribution coefficients ranging between 7 and 9, 114 thus being comparable to the two proposed solvents.…”
Section: Experimental Comparison With Cosmo-rs Predictions and Othermentioning
confidence: 80%
“…The authors claim that an autocatalytic effect takes place when operating with microwaves at 190°C during 3 h, reporting complete conversion of xylose with 78% selectivity; the authors also reported the use of MeTHF and isophorone as EP under the same conditions with lower performance. In addition, birch hydrolysate was employed as substrate with similar conversions and yields of 68% after only 1.5 h. 114 The biphasic dehydration of xylose with toluene as EP has been reported with different zeolites, where MOR-type M-20 (SiO 2 : Al 2 O 3 = 20 : 1) achieved 42% yield to furfural and 79% conversion of xylose after 3 h at 190°C in a screw-stirred autoclave. 115 Recently, a loading of 2.5 wt% of terephthalic acid obtained from waste polyethylene terephthalate has provided good results as catalyst in H 2 O/toluene medium leading to 71% yields at 190°C in 3 h, which was higher than when butyl acetate was the extracting agent in comparable reaction conditions, reaching 60%.…”
Section: Green Chemistry Critical Reviewmentioning
confidence: 96%
See 3 more Smart Citations